Lean Six Sigma For Dummies - Brenig-Jones, Martin; Dowdall, Jo (For Dummies, 2021)
Become a process improvement star with Lean Six Sigma! Thinking Lean? Not in terms of weight loss, but operational efficiency? Then you can get into the Lean mindset with Lean Six Sigma For Dummies. A popular process improvement strategy used in many corporations, Lean Six Sigma exemplifies eliminating waste and optimizing flow at an operational level. With the strategies outlined in this book, you'll have your projects, team, and maybe even your organization running at peak efficiency. Written by two experts that have been teaching Lean Six Sigma for over 20 years, Lean Six Sigma For Dummies explains the jargon surrounding this organizational practice, outlines the key principles of both Lean thinking and the Six Sigma process, and breaks it all down into easy-to-follow steps. Use Lean Six Sigma to develop a culture of continuous improvement Complete repetitive tasks through robotic process automation Assess how well your company and employees adapt to Lean Six Sigma Discover tips on how to implement Lean Six Sigma every day Find best practices to sustain ongoing improvements With handy checklists and helpful advice, Lean Six Sigma For Dummies shows you how to implement Lean Six Sigma in any industry, within any size organization. Pick up your copy to successfully lean into the Lean Six Sigma mindset yourself.